2014
DOI: 10.1155/2014/187467
|View full text |Cite
|
Sign up to set email alerts
|

Burkitt Lymphoma of Thyroid Gland in an Adolescent

Abstract: Burkitt Lymphoma is a highly aggressive form of non-Hodgkin's lymphoma that in nonendemic areas has abdominal primary sites. We report a very rare case of Burkitt lymphoma of the thyroid gland presenting as a rapidly growing thyroid swelling in a 14-year-old white Caucasian British male with no preexisting thyroid or medical problems. The diagnosis was confirmed by an open wedge biopsy following a fine needle aspiration. The patient was treated according to the Children's Cancer and Leukaemia Group guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“… Kalinyak et al [2006] [ 2 ] 53 M Tracheal compressive symptoms from a rapidly expanding thyroid mass 6 Burkitt lymphoma Rituxan and CHOP therapy, changed to hyper-CVAD-R chemotherapy. The patient also received a single dose of intrathecal methotrexate 27 Patient free of disease after end of treatment Kandil et al [2012] [ 10 ] 60 F Rapidly expanding thyroid mass with airway compression and difficulty in swallowing 8.7 Burkitt-like lymphoma (B-cell lymphoma, unclassifiable) Rituximab, Cyclophosphamide, Mensa, Vincristine and Doxorubicin Successfully treated with 1 cycle of appropriate therapeutic chemotherapy Cooper et al [2014] [ 14 ] 14 M Large predominantly left-sided firm thyroid swelling, with a 3-month history of malaise, lethargy, and weight loss 6.7 Burkitt lymphoma t (8; 14) COP and prednisolone followed by 2 courses of COPADM, prednisolone and two courses of CYM chemotherapy. This was accompanied by intrathecal chemotherapy 36 Disease free 3 years after end of treatment Yildiz et al [2012] [ 22 ] 31 M Rapidly enlarging mass on the fore neck 4 Burkitt lymphoma R-Hyper-CVAD therapy 6 PET-CT scans performed after chemotherapy and at the 6-month follow-up were normal Mweempwa et al [2013] [ 24 ] 58 F Background of benign goiter presented with a rapidly enlarging thyroid mass, causing dysphagia and dyspnea 8 Burkitt lymphoma t (8; 14) Modified Magrath protocol for Burkitt’s lymphoma, low risk disease, which involved having 3 cycles of R-CODOX-M 4 Complete resolution of the tumour mass, 4 weeks after end of treatment Liying et al [2014] [ 30 ] 8 M Mass in the right anterior neck with difficulty in swallowing 4 Burkitt lymphoma t (8; 14) Right lobe thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Kalinyak et al [2006] [ 2 ] 53 M Tracheal compressive symptoms from a rapidly expanding thyroid mass 6 Burkitt lymphoma Rituxan and CHOP therapy, changed to hyper-CVAD-R chemotherapy. The patient also received a single dose of intrathecal methotrexate 27 Patient free of disease after end of treatment Kandil et al [2012] [ 10 ] 60 F Rapidly expanding thyroid mass with airway compression and difficulty in swallowing 8.7 Burkitt-like lymphoma (B-cell lymphoma, unclassifiable) Rituximab, Cyclophosphamide, Mensa, Vincristine and Doxorubicin Successfully treated with 1 cycle of appropriate therapeutic chemotherapy Cooper et al [2014] [ 14 ] 14 M Large predominantly left-sided firm thyroid swelling, with a 3-month history of malaise, lethargy, and weight loss 6.7 Burkitt lymphoma t (8; 14) COP and prednisolone followed by 2 courses of COPADM, prednisolone and two courses of CYM chemotherapy. This was accompanied by intrathecal chemotherapy 36 Disease free 3 years after end of treatment Yildiz et al [2012] [ 22 ] 31 M Rapidly enlarging mass on the fore neck 4 Burkitt lymphoma R-Hyper-CVAD therapy 6 PET-CT scans performed after chemotherapy and at the 6-month follow-up were normal Mweempwa et al [2013] [ 24 ] 58 F Background of benign goiter presented with a rapidly enlarging thyroid mass, causing dysphagia and dyspnea 8 Burkitt lymphoma t (8; 14) Modified Magrath protocol for Burkitt’s lymphoma, low risk disease, which involved having 3 cycles of R-CODOX-M 4 Complete resolution of the tumour mass, 4 weeks after end of treatment Liying et al [2014] [ 30 ] 8 M Mass in the right anterior neck with difficulty in swallowing 4 Burkitt lymphoma t (8; 14) Right lobe thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, the thyroid gland does not contain native lymphoid tissue, therefore, the intrathyroid lymphoid tissue that causes thyroid lymphoma comes from the migration of lymphoid tissue into the thyroid during an inflammatory or immunologic process. The most common condition resulting in lymphoid migration is autoimmune thyroiditis (i.e., Hashimoto’s thyroiditis) [ 14 16 ]. Large adult population-based as well as retrospective clinicopathological case series suggest that primary thyroid Non-Hodgkin lymphoma NHL typically occur in middle to older-aged persons and have a predilection for females (it have also shown that patients with chronic lymphocytic thyroiditis have a greater risk of subsequently developing thyroid lymphoma when compared to age and gender matched normal individuals) [ 5 , 6 , 16 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these symptoms are not specific and they might also be due to other conditions, such as anaplastic carcinoma or Riedel’s thyroiditis. Moreover, sometimes, the thyroid mass due to a lymphoma can be an incidental occurrence in patients with fever, malaise, weight loss, or hypothyroidism due to Hashimoto’s thyroiditis, as reported by [ 9 , 16 , 20 ]. Otherwise, there have been also a few reports of exceptional presentations such as a pathological fracture due to a secondary lytic lesion [ 13 ], and the onset of diplopia and headache due to a bilateral cavernous sinus thrombosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This neoplasm is characterized by intermediate-sized lymphoid cells with a "starry sky" appearance and exhibits chromosomal translocations that activate the MYC oncogene [2,3]. To our knowledge, only 20 patients with primary thyroid BL have been described in the English-language literature [4][5][6][7][8][9][10][11][12][13][14][15][16]. Because of its extremely low prevalence, little is known about the pathogenesis and clinicopathological features of this disease, or about the differences between it and its systemic counterpart.…”
Section: Introductionmentioning
confidence: 99%